Modulation of Chloroquine in nanoparticle uptake: a review (Research, Society and Development, 2021)
The application of nanotechnology in several areas of medicine has been promising, however, there are still serious problems, such as in the area of oncology, for example. Although nanoparticles can accumulate 10 times more in tumors, less than 1% of the injected dose actually reaches the tumor, as they are retained mainly in the liver and spleen. Liver-specific macrophages, called Kupffer cells, are one of the main barriers to the use of nanoparticles for cancer treatment. These Kupffer Cells are part of the Mononuclear Phagocytic System (MPS) and exhibit endocytic activity against materials that pass through the blood and enter the liver. For this reason, Kupffer cells are central to the process of eliminating nanoparticles that cross the body's epithelial barriers. Still, chloroquine can act directly on the MPS, helping the nanoparticles reach their final target. This review addresses the main studies with chloroquine acting in the MPS, which could revolutionize cancer treatment or other biological applications.